BLACK LEADERSHIP IN ORGANIZATIONS: a survey on the challenges and advantages of racial diversity in organizations - da Silva Rodrigues, Samara; de Oliveira Silva, Daniel; Segnini Rodrigues, Lilian (Revista Interface Tecnológica, 2023)
Black people face numerous challenges in society and in the job market, including barriers to advancing in their careers. Two main reasons that prevent black individuals from holding leadership positions are structural racism and the 'whiteness pact'. The aim of this article is to analyze the representation of black leadership in organizations by investigating the perceptions and challenges faced by black people as leaders or in pursuing leadership roles. To achieve this, a questionnaire with both closed and open-ended questions was administered to black individuals—those of Black, Afro-Brazilian, or mixed-race descent. The results revealed the existence of barriers and prejudices that hinder the progression of black leaders, as well as a lack of representation in prominent positions. It is concluded that promoting diversity and inclusion within organizations is essential to create equitable opportunities for black leaders.
Keywords: Black leadership; Black individuals; Diversity; Inclusion